TECHNOLOGIES OF SPIRITUAL AND MORAL EDUCATION OF PRIMARY SCHOOL STUDENTS THROUGH LANGUAGE LESSONS - Nebaraeva Zebiniso (European Science Publishing, 2023)
In the oral art of the peoples of the world, the pedagogical ideas, worldview, spiritual experiences, spiritual and moral ideals, life experience, national traditions, values and philosophies of a people are described in exemplary and interesting stories, songs, tales and teachings of the people. In today's globalization process, the development of innovative models and mechanisms of spiritual and moral education of preschool children around the world, the improvement of scientific and methodological support of spiritual and moral education of preschool children in a healthy environment in accordance with pedagogical technologies and educational strategies. One of the current directions is to provide them with quality preparation for primary school education.
Keywords: National, cultural, resource, education, mechanism, innovation.